Effects of Zinc Phthalocyanine Photodynamic Therapy on Vital Structures and Processes in Hela Cells - Hosik, Jakub; Hosikova, Barbora; Binder, Svatopluk; Lenobel, Rene; Kolarikova, Marketa; Malina, Lukas; Dilenko, Hanna; Langova, Katerina; Bajgar, Robert; Kolarova, Hana (International journal of molecular sciences, 2024)
This work presents results on the efficiency of newly designed zinc phthalocyanine-mediated photodynamic therapy of both tumoral and nontumoral cell models using the MTT assay. Further detailed examinations of mechanistic and cell biological effects were focused on the HELA cervical cancer cell model. Here, ROS production, changes in the mitochondrial membrane potential, the determination of genotoxicity, and protein changes determined by capillary chromatography and tandem mass spectrometry with ESI were analyzed. The results showed that, in vitro, 5 Jcm-2 ZnPc PDT caused a significant increase in reactive oxygen species. Still, except for superoxide dismutase, the levels of proteins involved in cell response to oxidative stress did not increase significantly. Furthermore, this therapy damaged mitochondrial membranes, which was proven by a more than 70% voltage-dependent channel protein 1 level decrease and by a 65% mitochondrial membrane potential change 24 h post-therapy. DNA impairment was assessed by an increased level of DNA fragmentation, which might be related to the decreased level of DDB1 (decrease in levels of more than 20% 24 h post-therapy), a protein responsible for maintaining genomic integrity and triggering the DNA repair pathways. Considering these results and the low effective concentration (LC50 = 30 nM), the therapy used is a potentially very promising antitumoral treatment.
Keywords: DNA Damage; fotochemoterapie; Indoles; lidé; fotosenzibilizující látky; Membrane Potential, Mitochondrial; organokovové sloučeniny; Organometallic Compounds; reaktivní formy kyslíku; sloučeniny zinku; Photochemotherapy; HeLa Cells; poškození DNA; indoly; Photosensitizing Agents; Zinc Compounds; isoindoly; Humans; oxidační stres; HeLa buňky; Isoindoles; Oxidative Stress; membránový potenciál mitochondrií; Reactive Oxygen Species